Veil of winter [large type] - Dickerson, Melanie (Dickerson, Melanie. Dericott tales, 2024)
"Now available in trade paper from New York Times bestselling author Melanie Dickerson comes a reimagining of the beloved "Sleeping Beauty" tale. In the mountains near France, the medieval Princess Elyce is being forced to marry, thus forming an alliance that will enrich her father but enslave her kingdom. Instead, she chooses to feign her death and flee to Prague to beg King Wenceslaus to help save her people. In England, the young knight Sir Gerard has a vision from God instructing him to help Elyce on her quest. When he arrives to find she has been near death for days, he manages to revive her. However, thinking the stranger was trying to kiss her, the princess immediately distrusts him. But her desperate situation forces her to accept his aid. Pursued by her enemy's guards over mountainous terrain, they must also battle the deadly winter elements. Her greatest challenge may be to overcome the voices of disapproval and accusation from her childhood. Will her emotions lead her into her true identity, or will they undermine her ability to work with Gerard and to save her people, who desperately need her help?"--